HUBUNGAN PERILAKU BIDAN TERHADAP PENGGUNAAN ALAT PELINDUNG DIRI (APD) DALAM MENOLONG PERSALINAN NORMAL DI RUMAH SAKIT BENYAMIN GULUH KOLAKA - Nur Asmah; Sartiah Yusran; Ramadhan Tosepu; Adius Kusnan (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2021)
Occupational health and safety behaviour in hospitals is very important because the slightest action can pose a risk to midwives and patients. One of the causes of the risk of infection is the behaviour of midwives who at work do not wear complete personal protective equipment (PPE) where the prevention is more directed at the work environment, equipment. The purpose of this study was to determine the relationship between the behaviour of midwives on the use of personal protective equipment (PPE) in assisting normal delivery at Benyamin Guluh Kolaka Hospital with a cross-sectional design. The instrument used is a questionnaire. The results showed that there was a relationship between knowledge and behaviour of midwives on the use of PPE in Normal Delivery Assistance at Benyamin Guluh Kolaka Hospital. There is a relationship between attitudes and behaviour of midwives towards the use of PPE in Normal Delivery Assistance at Benyamin Guluh Kolaka Hospital. There is no relationship between compliance with the behaviour of midwives on the use of PPE in Normal Delivery Assistance at Benyamin Guluh Kolaka Hospital. There is a relationship between facilities and infrastructure and the behaviour of midwives towards the use of PPE in Normal Delivery Assistance at Benyamin Guluh Hospital.